Integrating Role of Sustainable Development Paradigm in Shaping the Human-landscape Relation - Bielińska, Elżbieta Jolanta; Futa, Barbara; Baran, Stanisław; Żukowska, Grażyna; Pawłowska, Małgorzata; Cel, Wojciech; Zhang, Tao (Problemy Ekorozwoju, 2015)
In order to implement the sustainable development paradigm more broadly, it is postulated to deviate from the simple protectionism, which is based on sectoral approach, in favour of systemic landscape management, which encompasses the human-landscape relations. The article presents the issues concerning rural landscape protection in Poland in relation to the assumptions of the European Landscape Convention. The aim of the article is to analyze the causes of inefficiency of the Polish rural landscape protection system.